Let's evaluate each equation to determine which one is not true.
A. \(-4 + (-3) = -7\)
Calculating:
\(-4 + (-3) = -4 - 3 = -7\)
This equation is true.
B. \(-8(2) = -16\)
Calculating:
\(-8 \times 2 = -16\)
This equation is true.
C. \(3 - (-2) = 5\)
Calculating:
\(3 - (-2) = 3 + 2 = 5\)
This equation is true.
D. \(-12 ÷ (-3) = -4\)
Calculating:
\(-12 ÷ (-3) = 4\)
This equation is not true because \(-12\) divided by \(-3\) equals \(4\), not \(-4\).
Therefore, the equation that is not true is D. \(-12 ÷ (-3) = -4\).